Modes of administration of nitric oxide devices and ventilators flow-by impact the delivery of pre-determined concentrations - Alice Vuillermoz; Mathilde Lefranc; Nathan Prouvez; Clément Brault; Yoann Zerbib; Mary Schmitt; Jean-Marie Forel; Mathieu Le Tutour; Arnaud Lesimple; Alain Mercat; Jean-Christophe Richard; François M. Beloncle (Annals of Intensive Care, 2024)
Abstract Background Nitric oxide (NO) is a strong vasodilator, selectively directed on pulmonary circulation through inhaled administration. In adult intensive care units (ICU), it is mainly used for refractory hypoxemia in mechanically ventilated patients. Several medical delivery devices have been developed to deliver inhaled nitric oxide (iNO). The main purpose of those devices is to guarantee an accurate inspiratory NO concentration, whatever the ventilator used, with NO2 concentrations lower than 0.3 ppm. We hypothesized that the performances of the different available iNO delivery systems could depend on their working principle and could be influenced by the ventilator settings. The objective of this study was to assess the accuracy of seven different iNO-devices combined with different ICU ventilators’ flow-by to reach inspiratory NO concentration targets and to evaluate their potential risk of toxicity. Methods We tested seven iNO-devices on a test-lung connected to distinct ICU ventilators offering four different levels of flow-by. We measured the flow in the inspiratory limb of the patient circuit and the airway pressure. The nitric oxide/nitrogen (NO/N2) flow was measured on the administration line of the iNO-devices. NO and NO2 concentrations were measured in the test-lung using an electrochemical analyzer. Results We identified three iNO-device generations based on the way they deliver NO flow: “Continuous”, “Sequential to inspiratory phase” (I-Sequential) and “Proportional to inspiratory and expiratory ventilator flow” (Proportional). Median accuracy of iNO concentration measured in the test lung was 2% (interquartile range, IQR -19; 36), -23% (IQR -29; -17) and 0% (IQR -2; 0) with Continuous, I-Sequential and Proportional devices, respectively. Increased ventilator flow-by resulted in decreased iNO concentration in the test-lung with Continuous and I-Sequential devices, but not with Proportional ones. NO2 formation measured to assess potential risks of toxicity never exceeded the predefined safety target of 0.5 ppm. However, NO2 concentrations higher than or equal to 0.3 ppm, a concentration that can cause bronchoconstriction, were observed in 19% of the different configurations. Conclusion We identified three different generations of iNO-devices, based on their gas administration modalities, that were associated with highly variable iNO concentrations’ accuracy. Ventilator’s flow by significantly impacted iNO concentration. Only the Proportional devices permitted to accurately deliver iNO whatever the conditions and the ventilators tested.